2015
DOI: 10.1016/j.ultrasmedbio.2014.12.668
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Microbubble Fragmentation, Deflation and Broadband Superharmonic Signal Production

Abstract: Acoustic angiography imaging of microbubble contrast agents utilizes the superharmonic energy produced from excited microbubbles, and enables high-contrast, high-resolution imaging. However, the exact mechanism by which broadband harmonic energy is produced is not fully understood. In order to elucidate the role of microbubble shell fragmentation in superharmonic signal production, simultaneous optical and acoustic measurements were performed on individual microbubbles at transmit frequencies from 1.75 to 3.75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 64 publications
2
42
0
Order By: Relevance
“…Although image intensity decreased rapidly with each subsequent scan (Figure 3), superharmonic echoes were detectable on the initial scan despite the fact that microbubbles had already been subjected to multiple pulses due to the large focal size of the low frequency transducer element ( Figure 1). This partial persistence of superharmonic signals over a few pulses is consistent with our own previous results [9]. We have also observed that superharmonic molecular imaging may be enhanced by using a microbubble population with a slightly larger diameter, consistent with previous observations that larger microbubbles improve sensitivity in conventional molecular imaging [10,12] and in acoustic angiography [8].…”
Section: A Bubble Destruction and Superharmonic Molecular Imagingsupporting
confidence: 92%
See 3 more Smart Citations
“…Although image intensity decreased rapidly with each subsequent scan (Figure 3), superharmonic echoes were detectable on the initial scan despite the fact that microbubbles had already been subjected to multiple pulses due to the large focal size of the low frequency transducer element ( Figure 1). This partial persistence of superharmonic signals over a few pulses is consistent with our own previous results [9]. We have also observed that superharmonic molecular imaging may be enhanced by using a microbubble population with a slightly larger diameter, consistent with previous observations that larger microbubbles improve sensitivity in conventional molecular imaging [10,12] and in acoustic angiography [8].…”
Section: A Bubble Destruction and Superharmonic Molecular Imagingsupporting
confidence: 92%
“…Additionally, larger bubbles are likely to produce superharmonic signals over a greater number of pulses than smaller bubbles [9]. In order to examine the effect of microbubble diameter on superharmonic imaging in vivo, two populations of microbubbles were prepared: a 1 μm population and a 4 μm population.…”
Section: B Microbubble Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbubbles having diameters of 1-4 μm were examined. Results indicate that production of a superharmonic signal was associated with two distinct physical behaviors: 1) immediate rupture of the microbubble shell, and 2) instantaneous decrease in shell diameter (at least 10%) in response to an acoustic pulse [63]. In the case of shell rupture, the amplitude of the superharmonic signal was approximately 4x higher than in the case of decrease in diameter.…”
Section: Physics Of Superharmonic Signal Productionmentioning
confidence: 91%